EFL learners’ perception and attitude in synchronous meetings through Zoom videoconferencing - Rojabi, Ahmad Ridho; Praptika Septi Femilia (JEES (Journal of English Educators Society), 2023)
Recently, incorporating technology in English as a foreign language (EFL) courses has been the topic of much debate. Technology can facilitate student interaction in the learning process and create an interactive and communicative classroom environment. Zoom is a solution for faculty members to engage and motivate students in virtual courses as it provides real interaction and direct feedback. This present study aimed to explore EFL students' perceptions as well as attitudes toward synchronous learning through Zoom Videoconferencing. The participants were 72 undergraduate students in the Intensive Reading course. The data was collected through questionnaires, observations, and interviews. The contents of the instrument were validated using expert judgment. The quantitative data were analyzed by using descriptive statistics while qualitative data were analyzed using thematic coding. The findings demonstrated that students had positive perceptions of Zoom videoconferencing in terms of actual use, perceived ease of use, intrinsic motivation, behavioral intention, and attitude. Further research into using Zoom videoconferencing to develop innovations in an online course is strongly recommended. HIGHLIGHTS: Zoom videoconferencing provides several benefits in terms of actual use, perceived ease of use, and satisfaction. Positive perceptions among students are related to their habits as digital natives and adjustments in post-pandemic classroom instruction which integrate technology in the educational setting. The learners’ positive attitude, they were satisfied with the course content, they felt comfortable participating in group discussions since the faculty designed interesting tasks and well-instructions and explanations. By doing so, this fun atmosphere in the teaching and learning process could promote peer interaction and build their social community. Synchronous videoconferencing can create an accessible, flexible, and effective classroom environment, facilitate an engaging online learning environment, and increase interactive and communicative interaction between teachers and students. By doing so, faculty members can create virtual courses utilizing Zoom videoconferencing for live interaction and an engaging classroom environment.